2014
DOI: 10.1007/s13197-014-1371-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soaking in noni (Morinda citrifolia) juice on the microbiological and color behavior of Haden minimally processed mango

Abstract: The purpose of this study was to evaluate the effect of soaking in noni juice on the microbiological and color behavior of minimally processed mango. Two batches of Haden mango cubes were treated by immersion in noni juice for 2.5 or 5.0 min. Each batch was packed in polypropylene boxes and stored at 6°C for up to 15 days; in addition, a control group of mango cubes was prepared by immersion in sterile water for the same duration. According to the results, the soaking of mango cubes in noni juice had an antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…In fruit farming, it was observed that the immersion of mango cubes in noni juice had an antimicrobial effect on mesophilic bacteria, molds and yeasts, demonstrating that this can be a potentially valuable technology for the decontamination of sliced fresh fruit surfaces (Ulloa et al , ).…”
Section: Antibacterial and Anti‐septic Activitiesmentioning
confidence: 99%
“…In fruit farming, it was observed that the immersion of mango cubes in noni juice had an antimicrobial effect on mesophilic bacteria, molds and yeasts, demonstrating that this can be a potentially valuable technology for the decontamination of sliced fresh fruit surfaces (Ulloa et al , ).…”
Section: Antibacterial and Anti‐septic Activitiesmentioning
confidence: 99%
“…Trans-ferulic acid (≥99% purity) was purchased from Sigma-Aldrich (Steinheim, Germany). Noni juice extract was kindly provided by the University of Nayarit, Mexico, and was prepared as described by Ulloa et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Fruits were carried to the laboratory of the Unidad de Tecnología de Alimentos of the Universidad Autónoma de Nayarit, in Tepic, Nayarit, Mexico. Fruits were washed with tap water; then, the fruit was placed in sealed plastic jars and left in natural fermentation into the dark for 60 days at 28 ± 3 °C [11,18]. Fermented juice was filtered and centrifuged for 15 min at 3,050 xg (Centrifuge 5804 R, Eppendorf AG, Germany).…”
Section: Noni Juice Preparationmentioning
confidence: 99%
“…In this regard, noni juice (NJ) has demonstrated an efficient activity for preserving sensory proprieties and microbiological control over fresh-cut fruits such as mango. e soaking of mango cubes in NJ had an antimicrobial effect for 15 days, reducing the count of aerobic mesophyllic, fungi, and yeast; besides, it maintained the color (CIE L * a * b * , Chroma, and Hue angle) during 12 days of storage [11].…”
Section: Introductionmentioning
confidence: 97%